A critical examination of policy objectives and instruments for a sustainable and inclusive post-pandemic recovery. Issue 2 (15th November 2021) - Tran-Nam, Binh; Le-Van, Cuong; Nguyen, Ngoc-Anh
Abstract : Purpose: This paper aims to provide rigor and clarity to the current coronavirus disease 2019 (COVID-19) policy debate in Vietnam. It is intended to serve a three-fold purpose. First, it critically examines the framing of policy objectives and the utilization of policy instruments for controlling COVID-19 in Vietnam. Second, it goes beyond policy design to consider the coordination and implementation of COVID-19 policies in Vietnam. Third, it discusses policy measures needed for post-COVID sustainable and inclusive growth, especially the sharing of the public costs of COVID-19 policies. Design/methodology/approach: The paper employs a positivist research framework that emphasizes the causal relationships between the variables under study. The method of analysis is mixed, combining both qualitative and quantitative techniques. In particular, a simple, theoretical model is constructed to evaluate the welfare effects of alternative vaccine strategies. No primary data were collected. Findings: The Vietnamese government's dual goals of containing the pandemic and maintaining economic growth, while being reasonable, need clarification and updating. It is argued that in the longer term, there is no trade-off between saving lives and protecting the economy. The downward revision of the projected growth rate and commitment to a coherent and transparent vaccination strategy is the best way to move forward in Vietnam. The choice of vaccine rollout order involves a consideration of ethics. It is suggested that it is appropriate to vaccinate elderly people and people with underlying medical conditions first. Complementary policy measures to stimulate aggregate demand and supply need to be expanded but also more targeted. Effective coordination and implementation of COVID-19 policies remain a serious challenge for Vietnam. Finally, inclusive growth and sustainable development should take account of human capital development and distributive justice. Social implications: The paper proposes a number of policy measures which have social impact. These include the government's formal commitment to a vaccine first strategy and a relief package of essential goods to poor and disadvantaged households. Originality/value: The paper contributes positively to the current COVID-19 policy formulation by providing rigor and clarity to the framing of policy objectives and the utilization of policy instruments. While vaccination has been adopted as a national policy instrument, its design and implementation can be much improved. The paper recommends an appropriate vaccine strategy for Vietnam. It also draws attention to other dimensions of successful policies, namely, communication, coordination, implementation and distributive justice.